The Effect Of Work Ability And Work Motivation On The Civil Servants Performance At The Department Of Education And Culture Of Central Bengkulu Regency - Yugianto Yugianto; Meiffa Herfianti; Rinto Noviantoro (Penerbit Jurnal Indonesia, 2021)
Performance is a very important thing in the company's efforts to achieve goals (Rivai, 2015: 86). Therefore, the management of an agency must try to encourage its employees to work well so that they can achieve the best performance. To create employee performance, of course, there are several things that must be considered by the agency, such as work ability and motivation. The purpose of this study is to determine the effect of work ability and work motivation on the civil servant performance at Department of Education and Culture of Central Bengkulu Regency. The sample in this study was 36 civil servants at the Department of Education and Culture of Central Bengkulu Regency. Collecting data using a questionnaire and the analytical method used is multiple linear regression, determination test and hypothesis testing. The results showed the regression value Y = 3.125 + 0.713X1 + 0.393X2 - with a positive regression direction, meaning that if work ability and job satisfaction increased, the performance of employees at the Department of Education and Culture of Central Bengkulu Regency would also increase. Work ability has a significant effect on employee performance at the Department of Education and Culture of Central Bengkulu Regency, because the significant value of 0.000 is smaller than 0.05. Work motivation has a significant effect on employee performance at the Department of Education and Culture of Central Bengkulu Regency, because the significant value of 0.005 is smaller than 0.05. Work ability and work motivation simultaneously have a significant effect on employee performance at the Department of Education and Culture of Central Bengkulu Regency because the significant value of 0.000 is smaller than 0.05. The coefficient of determination of R square is 0.666. This means that work ability and work motivation affect performance by 66.6% while the rest (100-66.6% = 33.4%) is influenced by other causal factors not examined in this study.